Pendampingan Pembuatan Aplikasi Sistem Pembayaran Digital (Qris) Pada Umkm Toko Kelontong - Avid Tri Asih; Ika Wulandari (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Community service activities aim to increase understanding and knowledge about digital or non-cash payment systems. This service was carried out at the MSMEs of the "Bu Yani" Grocery Store located in Karanglo, Argomulyo, Sedayu District, Bantul Regency and the MSMEs of the "Bu Ratmi" Grocery Store located in Balong, Kaligintung, Temon District, Kulon Progo Regency. The stages used in service activities are 1. Observation, 2. Presentation, 3. Training and Mentoring, 4. Evaluation. The result of this service activity is that MSME actors already understand QRIS and its benefits as an effective means of payment transactions, and the two grocery store MSMEs already have a new payment instrument with non-cash payments.